Pathophysiology of exercise-induced muscle damage and its structural, functional, metabolic, and clinical consequences - Stožer, A; Vodopivc, P; Križančić Bombek, L (Physiological research, 2020)
Extreme or unaccustomed eccentric exercise can cause exercise-induced muscle damage, characterized by structural changes involving sarcomere, cytoskeletal, and membrane damage, with an increased permeability of sarcolemma for proteins. From a functional point of view, disrupted force transmission, altered calcium homeostasis, disruption of excitation-contraction coupling, as well as metabolic changes bring about loss of strength. Importantly, the trauma also invokes an inflammatory response and clinically presents itself by swelling, decreased range of motion, increased passive tension, soreness, and a transient decrease in insulin sensitivity. While being damaging and influencing heavily the ability to perform repeated bouts of exercise, changes produced by exercise-induced muscle damage seem to play a crucial role in myofibrillar adaptation. Additionally, eccentric exercise yields greater hypertrophy than isometric or concentric contractions and requires less in terms of metabolic energy and cardiovascular stress, making it especially suitable for the elderly and people with chronic diseases. This review focuses on our current knowledge of the mechanisms underlying exercise-induced muscle damage, their dependence on genetic background, as well as their consequences at the structural, functional, metabolic, and clinical level. A comprehensive understanding of these is a prerequisite for proper inclusion of eccentric training in health promotion, rehabilitation, and performance enhancement.
Keywords: zánět; kosterní svaly; Muscle Contraction; bolest; Pain; Muscle, Skeletal; svalová kontrakce; lidé; Inflammation; cvičení; Humans; Exercise